Adaptations of interpersonal psychotherapy in psycho-oncology and its effects on distress, depression, and anxiety in patients with cancer: a systematic review - Laing, Ebba M.; Heinen, Jana M.; Acebo de Arriba, Rita; Schäffeler, Norbert; Zipfel, Stephan; Stengel, Andreas; Graf, Johanna (Frontiers in Psychology, 2024)
Objective. Patients with cancer experience significant psychosocial distress. Stressors include interpersonal difficulties like loneliness, isolation, thwarted belongingness, communication impediments, and conflicts. Interventions are required that address their specific psychosocial needs. Interpersonal Psychotherapy (IPT) is a promising concept for the treatment of psychosocial distress associated with cancer because it addresses patients' interactions and role transformations. This review aims to provide an overview of the current evidence regarding interventions for patients with cancer based on IPT.Methods. A systematic review following PRISM guidelines was conducted, including randomized controlled trials of IPT-based interventions in patients with cancer, assessing effects on distress, depression, and anxiety.Results. Eight studies were included, sampling 390 patients in total. Seven out of eight studies assessed exclusively women with breast cancer. Two studies described IPT interventions and showed stronger improvement in depression and anxiety compared to TAU and equal improvement in depression compared to other psychotherapy interventions. Six studies described remote Interpersonal Counselling (IPC). One found remote IPC to be superior to control conditions regarding depression, and one found remote IPC to be superior to attention control, but not active control conditions. No study found remote IPC to be superior to control conditions regarding distress.Discussion. There are few randomized controlled trials of IPT for patients with cancer. Results regarding depression and anxiety are promising for in-person IPT, but mixed for remote IPC.Conclusion. The review suggests in-person IPT, but not remote IPC, may yield benefits for patients with cancer. Research on the subject is scarce, and to inform implementation of IPT interventions, research with diverse groups of patients with cancer is required.